2014
DOI: 10.1080/10550887.2014.969599
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Substance Use Treatment: The Moderating Effects of Psychopathology on Treatment Outcomes

Abstract: The present study tested the influence of co-occurring mental health diagnoses on the relationship between length of stay and treatment outcome among adolescents residing in an inpatient substance abuse treatment facility. Data were collected via record review. Follow-up information was obtained at 7 days and 3 months post-discharge. Treatment outcome was defined as abstinence and engagement in recovery activities. Hierarchical linear regression demonstrated that comorbidities differentially moderated the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Second, it can address the poor, post-treatment relapse rates common among youth with substance use disorders. 14,63,80,81 To date, a handful of studies have evaluated treatment for youth with substance use disorders using EMA data, all with promising results.…”
Section: Technology-based Selective Preventionmentioning
confidence: 99%
“…Second, it can address the poor, post-treatment relapse rates common among youth with substance use disorders. 14,63,80,81 To date, a handful of studies have evaluated treatment for youth with substance use disorders using EMA data, all with promising results.…”
Section: Technology-based Selective Preventionmentioning
confidence: 99%
“…Researchers have denoted the need to refine adolescent addiction treatment to enhance engagement and treatment completion, as well as recovery-related outcomes (4,5). In 2018, approximately one in 26 adolescents in the United States needed treatment for a substance use disorder and related symptoms; however, the data showed that only approximately 16.8% received services (2).…”
Section: Introductionmentioning
confidence: 99%
“…For those adolescents that use treatment, programs are often building on singular treatment modalities. Despite these treatment modalities with moderate efficacy, adolescents with addiction continue to disengage early from treatment, and overall outcomes can still improve (4). To this end, previous literature has suggested Copyright © 2020, Author(s).…”
Section: Introductionmentioning
confidence: 99%
“…Psychopathologies include emotional and behavioral problems such as anxiety or deviant behavior [7,8], and can be divided into externalizing and internalizing pathologies. They represent distinct obstacles for SUD therapy [9][10][11] that might need clinical attention already during SUD treatment [12][13][14]. Externalizing problems such as aggressive behavior during social interactions might be shown in intervention settings, too, thereby complicating therapeutic relationships and increasing the risk for unsuccessful treatments [15].…”
Section: Introductionmentioning
confidence: 99%